13 Reasons Why Not: A Methodological and Meta‐Analytic Review of Evidence Regarding Suicide Contagion by Fictional Media. Issue 4 (14th October 2018) - Ferguson, Christopher J.
Abstract : Background: For decades, policymakers and suicide prevention advocates have questioned whether exposure to media with suicide themes, whether television, movies, or music, could increase suicide risk among youth. To date, no clear picture has emerged, with data inconsistent Aims: To access whether current evidence can support concerns that fictional media increases risk of viewer suicidal ideation. Materials & Methods: Two broad forms of data consider the issue, namely society‐level aggregate data, and data from smaller correlational and experimental studies. The current article examined the evidence for suicide contagion by fictional media with a methodological and meta‐analytic review. Results: Results suggest that current data do not support the theory that suicide contagion by fictional media occurs. Discussion: In addition to lack of consistency in current research results, widespread methodological concerns limit confidence in conclusions from many studies. A commitment to better methods and open science is warranted. Conclusion: It is recommended that individuals exercise caution in public statements linking suicide‐themed fictional media to suicide contagion as data may not be able to support such claims.